2022
DOI: 10.3390/su14106096
|View full text |Cite
|
Sign up to set email alerts
|

Land and Water Productivity in Intercropped Systems of Walnut—Buckwheat and Walnut–Barley: A Case Study

Abstract: Intercropping arable crops in orchards is a sustainable land use for intensifying agricultural production, under the condition of plants’ complementarity in sharing resources. This study investigated the aspects of water use and yields in intercropped systems of walnut and crops. To assess possible temporal complementarity between crops and trees, a summer crop—buckwheat—and a winter crop—barley—were intercropped in walnut orchards. The land and water productivity were studied under two designs: in an older, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…LER was always greater than 1 and ranged from 1.57 (AFSO-ICBA-Q5) to 2.07 (AFSO-Puno), indicating that the productivity was 57% to 107% higher in AFS than SCS. Similar findings were reported by [5,22,26,58,59] when growing other annual crops within fruit tree-based agroforestry.…”
Section: Crop Water Productivity (Cwp) and Land Equivalent Ratio (Ler)supporting
confidence: 84%
“…LER was always greater than 1 and ranged from 1.57 (AFSO-ICBA-Q5) to 2.07 (AFSO-Puno), indicating that the productivity was 57% to 107% higher in AFS than SCS. Similar findings were reported by [5,22,26,58,59] when growing other annual crops within fruit tree-based agroforestry.…”
Section: Crop Water Productivity (Cwp) and Land Equivalent Ratio (Ler)supporting
confidence: 84%
“…The state government of Himachal Pradesh has allocated funds to support ZBNF and the Gujarat, Meghalaya and Rajasthan state governments have also committed to setting up programs for ZBNF. Study reported that practicing of AF in place of mono-cropping has enhanced 53% more productivity and 83% more water-efficiency as compared to mono-cropping [17]. This hints AF assisted NF to solve socio-economic and agro ecological challenges faced by neglected smallholding farmers of dry land.…”
Section: Nf To Double the Farmers' Incomementioning
confidence: 96%
“…Less environmental pollution which maintains climate health and services [57] and nutrient cycling with minimal cash inputs to farm [17,19]. Leguminous tress such as Acacia species improve soil quality by nutrient enrichment and provides many valuable products like gum, Cutch and Katha [20].…”
Section: Climate Services Intensive Use Of Chemical Fertilizer Leads ...mentioning
confidence: 99%
“…However, intercropping is not always a good idea. Žalac et al. (2022) checked land and water productivity (WP) in an old and dense orchard compared to a younger one, both with intercropping buckwheat or barley and walnut trees, and found a reduction in walnut yields and WP due to competition between crops in old orchards, although buckwheat productivity reached the highest yield and WP in the young orchard.…”
Section: Using Buckwheat In Agroecology and Organic Farming For Weed ...mentioning
confidence: 99%